Multiplier Sequence Spaces Defined by Statistical Summability and Orlicz-Pettis Theorem. (23rd August 2021) - Kama, Ramazan; Altay, Bilal
Abstract: In this paper, we introduce some new multiplier spaces related to a series ∑ i x i in a normed space X through f – statistical summability and give some characterizations of completeness and barrelledness of the spaces through weakly unconditionally Cauchy series in X and X *, respectively. We also obtain a new version of the Orlicz-Pettis theorem within the frame of the f – statistical convergence.